Myocyte Remodeling Due to Fibro-Fatty Infiltrations Influences Arrhythmogenicity - De Coster, Tim; Claus, Piet; Seemann, Gunnar; Willems, Rik; Sipido, Karin R.; Panfilov, Alexander V. (Frontiers in Physiology, 2018)
The onset of cardiac arrhythmias depends on the electrophysiological and structural properties of cardiac tissue. Electrophysiological remodelling of myocytes due to the presence of adipocytes constitutes a possibly important pathway in the pathogenesis of atrial fibrillation. In this paper we perform an in-silico study of the effect of such myocyte remodelling on the onset of atrial arrhythmias and study the dynamics of arrhythmia sources --- spiral waves. We use the Courtemanche model for atrial myocytes and modify their electrophysiological properties based on published cellular electrophysiological measurements in myocytes co-cultered with adipocytes (a $69-87 %$ increase in $APD_{90}$ and an increase of the RMP by $2.5-5.5 mV$.). In a generic 2D setup we show that adipose tissue remodelling substantially affects the spiral wave dynamics resulting in complex arrhythmia and such arrhythmia can be initiated under high frequency pacing if the size of the remodelled tissue is sufficiently large. These results are confirmed in simulations with an anatomically accurate model of the human atria.